Penelitian Arsitektur Studi Kasus: Evaluasi Kenyamanan Termal dan Kebisingan pada Ruang Kerja Direktorat Perundingan ASEAN - Septiva Setia Putri; Nazaruddin Khuluk (Universitas Krisnadwipayana, Fakultas Teknik Program Studi Arsitektur, 2025)
This study evaluates thermal comfort and noise levels in the workspace of the ASEAN Negotiation Directorate at the Ministry of Trade of the Republic of Indonesia. Indoor environmental comfort significantly affects employee productivity and health, yet it often declines due to spatial layout changes and suboptimal HVAC system performance. The research method involves direct measurements of air temperature, relative humidity, and noise levels using standard instruments, as well as the collection of employee perceptions through questionnaires. The measured data are analyzed and compared with the Indonesian National Standards (SNI 03-6572-2001 for thermal comfort and SNI 03-6386-2000 for noise comfort). The results of this study are expected to provide recommendations for improving the quality of the working environment through enhancements to the ventilation system and the acoustic design of the workspace.